2009-05-13T19:59:42+02:00
1) 3x=3-->x=1
2)2=7y-->y=2/7
3)2x=1-->x=1/2
4)2x=2-->x=1
5)5x=-10-->x=-2
2009-05-13T20:01:36+02:00
1)
3x=9-6
3x=3
x=1
2)
5-3=7y
7y=2
y=2/7
3)
-2x=-1
x=1/2
4)
2x+2=4
2x=2
x=1
5)
6x+9=x-1
5x=-10
x=-2
2009-05-13T20:03:15+02:00
1.
3x + 6 = 9
3x=3
x=1
2. 5= 3+7y
3+7y=5
7y=2
y=2/7
3. -x-3 = x - 4
-2x=-1
x=1/2
4. 2 ( x+1 ) = 4
2x+2=4
2x=2
x=1
5. 3 ( 2x+3 ) = x - 1
6x+9=x-1
5x=-10
x=-2
2009-05-13T20:03:43+02:00
1. 3x+6=9
3x=9-6
3x=3 / 3
x=1

2. 5=3+7y
7y= 5-3
7y=2 / 7
y= 2:7

3. -x-3 = x - 4
-x-x= -4 + 3
-2x= -1 / -2
x= ½

4. 2 ( x+1 ) = 4
2x+2=4
2x=4-2
2x=2 / 2
x=1

5. 3 ( 2x+3 ) = x - 1
6x+9 = x-1
6x-x= - 1 - 9
5x= -10 / 5
x= - 2
2009-05-13T20:04:03+02:00
A)3x+6=9
3x=9-6
3x=3 /3
x=1

b)5=3+7y
5-3=7y
2=7y /7
2/7=y

c)-x-3=x-4
-x-x=-4+3
-2x=-1 /-2
x=1/2

d)2(x+1)=4
2x+2=4
2x=4-2
2x=2 /2
x=1

e)3(2x+3)=x-1
6x+9=x-1
6x-x=-1-9
5x=-10 /5
x=-2
2009-05-13T20:04:22+02:00
1, 3x+6=9 I-6
3x=3 I/3
x=1

2, 5=3+7y
7y+3=5 I-3
7y=2 I/7
y=2/7

3, -x-3=x-4 I+3
-x=x-1 I-x
-2x=-1 I/-2
x=-1/2

4, 2(x+1)=4
2x+2=4 I-2
2x=2 I/2
x=1

5, 3(2x+3)=x-1
6x+9=x-1 I-9
6x=x-10 I-x
5x=-10 I/5
x=-2
2009-05-13T20:10:02+02:00
1. 3x+6=9
3x=9-6 /÷3
x= 1
2. 5=3+7y
-7y=3-5 /÷ (-7)
y= ²/₇
3. -x-3=x-4
-x-x=-4+3
-2x= -1 /÷(-2)
x= ½
4.2(x+1) =4
2x+2=4
2x=2 /÷2
x=1
5. 3(2x+3) =x-1
6x+9=x-1
6x-x= -1 -9
5x= -10 /÷5
x= -2
2009-05-13T20:16:50+02:00
1. 3x+6=9
3x=9-6
3x=3|:3
x=1

2. 5=3+7y
7y=5-3
7y=2|:7
y=0,28

3. -x-3=x-4
-x-x=-4+3
-2x=-1|:(-2)
x=0,5

4. 2(x+1)=4
2x+2=4
2x=4-2
2x=2|:2
x=1

5. 3(2x+3)=x-1
6x+9=x-1
6x-x=-1-9
5x=-10|:5
x=-2